Thermal degradation of Affinisol HPMC: Optimum Processing Temperatures for Hot Melt Extrusion and 3D Printing - Svoboda, Roman; Nevyhoštěná, Marie; Macháčková, Jana; Vaculík, Jan; Knotková, Kateřina; Chromčíková, Maria; Komersová, Alena (Pharmaceutical research, 2023)
PURPOSE: Affinisol HPMC HME is a new popular form of hypromellose specifically designed for the hot melt extrusion and 3D printing of pharmaceutical products. However, reports of its thermal stability include only data obtained under inert N2 atmosphere, which is not consistent with the common pharmaceutical practice. Therefore, detailed investigation of its real-life thermal stability in air is paramount for identification of potential risks and limitations during its high-temperature processing. METHODS: In this work, the Affinisol HPMC HME 15LV powder as well as extruded filaments will be investigated by means of thermogravimetry, differential scanning calorimetry and infrared spectroscopy with respect to its thermal stability. RESULTS: The decomposition in N2 was proceeded in accordance with the literature data and manufacturer's specifications: onset at ~260°C at 0.5°C·min-1, single-step mass loss of 90-95%. However, in laboratory or industrial practice, high-temperature processing is performed in the air, where oxidation-induced degradation drastically changes. The thermogravimetric mass loss in air proceeded in three stages: ~ 5% mass loss with onset at 150°C, ~ 70% mass loss at 200°C, and ~ 15% mass loss at 380°C. Diffusion of O2 into the Affinisol material was identified as the rate-determining step. CONCLUSION: For extrusion temperatures ≥170°C, Affinisol exhibits a significant degree of degradation within the 5 min extruder retention time. Hot melt extrusion of pure Affinisol can be comfortably performed below this temperature. Utilization of plasticizers may be necessary for safe 3D printing.
Keywords: farmaceutická chemie; 3D tisk; Hot Temperature; affinisol; hot melt extrusion; DSC; vysoká teplota; thermal degradation; Solubility; Temperature; TGA; rozpustnost; Chemistry, Pharmaceutical; teplota; technologie extruze tavenin; Hot Melt Extrusion Technology; Printing, Three-Dimensional